2017
DOI: 10.1016/j.scitotenv.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of pharmaceuticals and personal care products (PPCPs) and artificial sweeteners (ASs) as wastewater indicators in the Pearl River Delta, South China

Abstract: Wastewater indicator is a useful tool for evaluating the wastewater impact on natural water, but there is little information about the suitability of wastewater indicators for different regions. This study aimed to select suitable wastewater indicators in the Pearl River Delta region, south China by screening a range of wastewater related organic compounds. The screening campaign was carried out by investigating the occurrence and removal efficiencies of 93 pharmaceuticals and personal care products (PPCPs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(56 citation statements)
references
References 42 publications
0
47
1
2
Order By: Relevance
“…Although previous studies documented minimal ACE degradation in wastewater treatment plants, (Buerge et al, 2009;Scheurer et al, 2009), recent studies (Castronovo et al, 2017;Yang et al, 2017) found that ACE degradation can be significant in some wastewater treatment systems. Even so, Yang et al (2017) show that ACE concentrations in effluent can remain very high compared with other potential organic wastewater tracers, only being surpassed by erythromycin-H 2 O and SUC in a study of nine wastewater treatment plants in China. Acesulfame appears to be very resistant to degradation once released into the environment and therefore can be used to track wastewater far from its source.…”
Section: Artificial Sweeteners Reveal Septic System Effluent In Ruralmentioning
confidence: 98%
See 1 more Smart Citation
“…Although previous studies documented minimal ACE degradation in wastewater treatment plants, (Buerge et al, 2009;Scheurer et al, 2009), recent studies (Castronovo et al, 2017;Yang et al, 2017) found that ACE degradation can be significant in some wastewater treatment systems. Even so, Yang et al (2017) show that ACE concentrations in effluent can remain very high compared with other potential organic wastewater tracers, only being surpassed by erythromycin-H 2 O and SUC in a study of nine wastewater treatment plants in China. Acesulfame appears to be very resistant to degradation once released into the environment and therefore can be used to track wastewater far from its source.…”
Section: Artificial Sweeteners Reveal Septic System Effluent In Ruralmentioning
confidence: 98%
“…Once in the environment, numerous factors can control the fate of artificial sweeteners. Saccharin (SAC) and cyclamate (CYC) have generally been found to be more easily degraded than SUC and ACE (Buerge et al, 2009; Scheurer et al, 2009; Robertson et al, 2013) and have been proposed as tracers of untreated or undertreated wastewater (Buerge et al, 2009; Yang et al, 2017). For example, Zirlewagen et al (2016) used CYC/ACE ratios to distinguish between “old or treated wastewater” and “fresh and untreated wastewater.” The presence of the more degradable artificial sweeteners in groundwater can be an indication of more recent contamination and proximity to the effluent source.…”
mentioning
confidence: 99%
“…Specifically more and more researchers have shed light on chemical or biological marker species to identify and quantify sewage source discharge. For example, many researchers demonstrated that PPCPs, artificial sweeteners and inorganic ions such as potassium, chloride and sodium, could serve as promising markers of sewage contamination [9][10][11][12][13][14][15][16]. However, no published literatures were found concerning the use of markers in identifying surface water intrusion into the storm pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Eclética Química Journal, vol. 44, n. 1, 2019, 40-52 ISSN: 1678-4618 DOI: 10.26850/1678-4618eqj.v44.1.2019.p40-52 remediation methods, leading to their omnipresence in pharmaceutical wastewaters 7,8 .…”
Section: Introductionmentioning
confidence: 99%